Exposure enhanced photoluminescence of CdS0.9Se0.1 quantum dots embedded in spin-coated Ge25S75 thin films. Issue 85 (22nd November 2017) - Slang, Stanislav; Loghina, Liudmila; Palka, Karel; Vlcek, Miroslav
Abstract : Semiconductor quantum dots (QDs) are well known photoluminescent materials. Abstract : Semiconductor quantum dots (QDs) are well known photoluminescent materials. Their potential practical applications depend on their physico-chemical and luminescent properties and also on the properties of hosting material. To ensure that QDs retain their photoluminescence during the preparation of a suitable solid composite form, the solution based casting techniques with deposition at lower temperatures are usually used. In our work, we have doped an inorganic Ge25 S75 chalcogenide glass matrix with synthesized CdS0.9 Se0.1 QDs and prepared thin films by the solution based spin-coating technique. In comparison with commonly used polymers the Ge25 S75 chalcogenide glass thin films a possess high refractive index and wide VIS-NIR-MIR optical transparent region. We also report on the phenomenon of significant UV exposure induced increase of doped thin film photoluminescence intensity which can be exploited in local photo-induced photoluminescence enhancement of doped chalcogenide glass thin films.